2004
DOI: 10.1074/jbc.m308673200
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin-Dockerin Interactions within and between Clostridium josui and Clostridium thermocellum

Abstract: The cellulosome components are assembled into the cellulosome complex by the interaction between one of the repeated cohesin domains of a scaffolding protein and the dockerin domain of an enzyme component. We prepared five recombinant cohesin polypeptides of the Clostridium thermocellum scaffolding protein CipA, two dockerin polypeptides of C. thermocellum Xyn11A and Xyn10C, four cohesin polypeptides of Clostridium josui CipA, and two dockerin polypeptides of C. josui Aga27A and Cel8A, and qualitatively and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…The preference in favor of the C. thermocellum system can be explained by the superior affinity characteristics for the cohe- sin-dockerin interaction of the latter over those of C. cellulolyticum, as observed previously (5,15,(21)(22)(23). In any case, Sw1-2, which contains both the first and last third of the C. thermocellum cohesin, binds strongest to the corresponding dockerin.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…The preference in favor of the C. thermocellum system can be explained by the superior affinity characteristics for the cohe- sin-dockerin interaction of the latter over those of C. cellulolyticum, as observed previously (5,15,(21)(22)(23). In any case, Sw1-2, which contains both the first and last third of the C. thermocellum cohesin, binds strongest to the corresponding dockerin.…”
Section: Resultsmentioning
confidence: 58%
“…Initial studies on the cohesin-dockerin interaction from different species indicated a general lack of intraspecies specificity (4 -6), whereas between species the interaction appeared to be selective (5,7). This rule usually prevails within a given scaffoldin, but not among different scaffoldins, even those produced by the same species (26 -30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction was determined by the addition of 100 l of the desired competitor samples (the ExgS wild-type dockerin protein, up to a maximum of 1.3 M), immediately followed by the addition of 100 l of a solution of wild-type and modified EngH, ExgS and EngE to a final concentration of 47 nM. The running buffer contained 10 mM CaCl 2 because calcium ions are required for the binding of cellulosomal enzymes to the cohesin modules [12]. Dilutions of the competitor were obtained using TrisNC buffer containing BSA to maintain a constant protein concentration.…”
Section: Competitive Enzyme-linked Interaction Assay (Celia)mentioning
confidence: 99%
“…The known number of dockerin-bearing enzymes in C. thermocellum was reported to be approximately eight times higher than the number of cohesins in the scaffoldin subunit (Shoham et al 1999). A few reports have demonstrated that several cellulosomal catalytic units containing dockerin I modules can bind to cohesin I modules from other Clostridiums (Jindou et al 2004;Pinheiro et al 2009;Sakka et al 2009). This may also contribute to the integral increase in FPA.…”
Section: Transcriptional Changes In Cellulosomal Components and Noncementioning
confidence: 99%